Trade Openness and Growth : Pursuing Empirical Glasnost - Billmeier, Andreas (IMF Working Papers; Working Paper, 2007)
Studies of the impact of trade openness on growth are based either on cross-country analysis-which lacks transparency-or case studies-which lack statistical rigor. We apply transparent econometric methods drawn from the treatment evaluation literature to make the comparison between treated (i.e., open) and control (i.e., closed) countries explicit while remaining within a unified statistical framework. First, matching estimators highlight the rather far-fetched country comparisons underlying common cross-country results. When appropriately restricting the sample, we confirm a positive and significant effect of openness on growth. Second, we apply synthetic control methods-which account for endogeneity due to unobservable heterogeneity-to countries that liberalized their trade regime and we show that trade liberalization has often had a positive effect on growth.